Postmodernism and Gandhi - Upāsanā Pāṇḍeya (Rawat Publications, 2010)
This study is a comprehensive and lucid account of the views of Mahatma Gandhi on the central themes of the human condition. The book provides a critical exposition of the emergence, evolution, and growth of the modernist and postmodernist world outlook in Western philosophical thought. The author rightly points out that Gandhi's ideas of Swaraja, Ahimsa, and Satyagraha provide not only a critique, but also an alternative, to modernity. Since Gandhi was critical of many evil practices - such as untouchability, social stratification, and oppression of women - many interpreters tend to interpret Gandhi as a modern thinker. However, the analysis in this book demonstrates that Gandhi was neither a modernist nor a postmodernist thinker. In fact, any attempt to place Gandhi in such categories would miss the richness and uniqueness of Gandhi's theory and practice. In view of the lucidity, clarity of thought, depth of comprehension, soundness of exposition and interpretation, the book will prove relevant on the contemporary discourse of postmodernism and Gandhi.